2002
DOI: 10.1046/j.1365-2141.2002.03239.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine for the treatment of hepatitis B virus reactivation following chemotherapy for non‐Hodgkin's lymphoma

Abstract: Summary. Chemotherapy for non-Hodgkin's lymphoma (NHL) patients with chronic hepatitis B virus (HBV) infection may be accompanied by severe hepatitis. Of 86 consecutive NHL patients, 11 (12á8%) exhibited a positive serum HBsAg. Six of these patients (54á5%) developed acute exacerbation of chronic HBV infection following chemotherapy and received lamivudine. Five of the six patients demonstrated a clinical improvement, one patient died from fulminant hepatic failure owing to delayed lamivudine therapy and poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 13 publications
1
66
0
3
Order By: Relevance
“…Prophylactic treatment with antiviral nucleotide analogue lamivudine prior to the start of chemotherapy has been suggested to be effective in reducing the incidence of HBV reactivation (Rossi et al, 2001;Liao et al, 2002;Lim et al, 2002;Persico et al, 2002;Shibolet et al, 2002;Yeo et al, 2002). The use of the proposed predictive model may aid the identification of high-risk patients who stand to benefit most from the antiviral, which could in turn be administered in a most cost-effective manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic treatment with antiviral nucleotide analogue lamivudine prior to the start of chemotherapy has been suggested to be effective in reducing the incidence of HBV reactivation (Rossi et al, 2001;Liao et al, 2002;Lim et al, 2002;Persico et al, 2002;Shibolet et al, 2002;Yeo et al, 2002). The use of the proposed predictive model may aid the identification of high-risk patients who stand to benefit most from the antiviral, which could in turn be administered in a most cost-effective manner.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HBV reactivation in hepatitis B surface antigen (HBsAg) seropositive cancer patients undergoing cytotoxic chemotherapy has been reported to be 20% or higher (Lok et al, 1991;Nokamura et al, 1996;Kumagai et al, 1997;Markovic et al, 1999;Yeo et al, 2000a). No preventive measures have been proven to prevent or reduce the incidence of HBV reactivation, although more recent reports have suggested that the prophylactic use of the antiviral agent lamivudine, prior to the start of chemotherapy, may reduce the occurrence of the condition (Rossi et al, 2001;Liao et al, 2002;Lim et al, 2002;Persico et al, 2002;Shibolet et al, 2002;Yeo et al, 2002). There has also been concern about the emergence of viral mutant as a result of lamivudine therapy, and, to date, limited data are available on the clinical impact of these mutants in immunosuppressed subjects.…”
mentioning
confidence: 99%
“…Also, not all patients could withstand percutaneous liver biopsy as they might have clotting derangement, especially those with hematological malignancy [83]. Another viral factor that has been investigated is hepatitis B e antigen (HBeAg) but the results are conflicting [6,10,58,89,[93][94][95]. This is probably related to the presence of the precore/core promoter HBV mutants (i.e., HBeAg-negative/hepatitis B e antigen-positive chronic hepatitis B infection) [96].…”
Section: Risk Factors Involved In Hbv Reactivationmentioning
confidence: 99%
“…As hepatitis due to HBV virological reactivation is associated or preceded by enhanced HBV viral replication during the immunosuppressive phase, the initiation of antiviral treatment such as lamivudine [102][103][104][105][106][107][108][109] and famciclovir [84,110] (Table 2). A meta-analysis of these 13 studies with 702 HBsAg-positive patients (237 treated with preemptive lamivudine and 465 untreated controls), showed that the incidence of hepatitis due to HBV reactivation was 3.3% in the treated group and 35.0% in the untreated control group (odds ratio [OR]: 0.083; 95% CI: 0.045-0.155, P \ 0.0001).…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
“…Most cases of HBV reactivation occur after the first two or three chemotherapy cycles [7,18]. Lamivudine can suppress viral replication as early as 1 week after its commencement.…”
Section: Reactivation Of Hepatitis B In Patients With Chronicmentioning
confidence: 99%